The impact of daily habits and lifestyle on the health and well-being of young adults aged 16-18 years - Kushta, Entela; Elmazi, Rovena; Mara, Ferdinand; Lile, Anduela; Pogoni, Junida; Çobaj, Jorida; Xhebexhiu, Klajdi (Edelweiss Applied Science and Technology, 2025)
Adolescence is a critical stage of development, marking the shift from childhood dependence to adult independence. This study explores the behaviors of adolescents aged 16–18 in Albania, focusing on nutrition, physical activity, and substance use. The goal is to highlight current health trends among youth, stress the importance of preventive education, and provide recommendations to improve adolescent well-being through informed policies and practices. A structured questionnaire was administered to 1,044 high school students from various cities in Albania. It addressed dietary habits, physical activity, and the use of tobacco, alcohol, and other substances. Data were analyzed using SPSS software to evaluate response patterns and percentages. Findings reveal that 60% of adolescents do not consume three regular meals a day and often prefer fast and processed foods. Additionally, 67% consume insufficient fruits and vegetables, while 60% include carbonated drinks in their daily diet. Substance use is also a concern: 83% have tried electronic cigarettes at least once, and 27% reported using marijuana or other soft drugs. These results underline the need for targeted interventions. Encouraging healthy eating, regular physical activity, and awareness of substance-related risks, alongside school-based education and supportive policies, is essential to promote long-term health and quality of life in youth.